ТРАДИЦІЙНІ МЕТОДИ ФОРМУВАННЯ ФІЗИЧНОЇ КУЛЬТУРИ СТУДЕНТСЬКОЇМОЛОДІ ВНЗ У ПРОЦЕСІ ПОЗААУДИТОРНОЇ СПОРТИВНО-МАСОВОЇ РОБОТИ - Довгань, Надія (Збірник наукових праць Уманського державного педагогічного університету, 2020)
У статті розкрито традиційні методи формування фізичної культури студентської молоді ВНЗ. Наведено класифікації означених методів у процесі позааудиторної спортивно-масової роботи. В основу класифікаційної моделі покладено спрямованість особистості: набуття та оволодіння знаннями, навчання руховим вміннями та навичкам, удосконалення рухових навичок і розвиток фізичних здібностей. Охарактеризовано групи методів, представлені в класифікаційній моделі. Зазначено чинники рухової активності. Визначено педагогічні умови вибору конкретного традиційного методу. В статье раскрыто традиционные методы формирования физической культуры студенческой молодежи вузов. Приведены классификации указанных методов в процессе внеаудиторной спортивно-массовой работы. В основу классификационной модели положено направленность личности: приобретение и овладение знаниями, обучение двигательным умениями и навыкам, совершенствование двигательных навыков и развитие физических способностей. Охарактеризованы группы методов, представленные в классификационной модели. Указано факторы двигательной активности. Определены педагогические условия выбора конкретного традиционного метода. The article deals with the traditional methods of formation of university students’ physical culture. The classification of the aforementioned methods in the extracurricular sports work is offered. Into the basis of the classification model, the orientation of a personality is laid: the acquisition and mastery of knowledge, learning and improving motor skills and the development of physical abilities. The characteristic of methods are presented in the classification model. There were distinguished the factors of physical activity, aimed at achievement of life, professional and communication skills, abilities to make independent decisions, high efficiency of working, harmonious constitution, beauty and aesthetics motor actions, which form an important area of motivation to regular physical training and sports. Pedagogical conditions of choice of the traditional method are investigated. These methods enable students to acquire holistic arsenal of new motor abilities and skills, to expand the range of motor actions to increase sportsmanship during extracurricular sports work.